(untitled) (Academicia Globe: Inderscience Research, 2021)
The main directions of economic and social development of Uzbekistan for the period until 2025 and the construction development program in the light of the Decrees of the President of the Republic of Uzbekistan emphasize the solution of the most important tasks of capital construction - reducing the cost of building materials, products and structures by reducing the materials-intensive products, saving raw materials, fuel, energy, metal, cement and other building materials, which helps reduce the cost of buildings and structures, reduce specific.